Perceptions about brain health among the United Arab Emirates population using the global brain survey: a cross-sectional study - Elbarazi, Iffat; Abdullahi, Aminu S.; Abdel Aziz, Karim; Stip, Emmanuel; Elkonaisi, Ismail; Fahim, Fayeza; Asghar, Maryum; Budin-Ljøsne, Isabelle; Nauman, Javaid (Frontiers in Public Health, 2025)
IntroductionInterest in brain health and general well-being research has increased due to advances in neurosciences, and aging population’s need for preventive health measures. However, there is limited research on perceptions and attitudes toward brain health in the United Arab Emirates (UAE), a country with a unique demographic and cultural context. We aimed to assess self-reported practices, beliefs and attitudes toward brain health within the UAE population, identifying key factors influencing these views, and contributing to the global understanding of brain health in non-Western, high-income settings.MethodsWe conducted a cross-sectional study using the UAE-adapted Global Brain Health Survey, originally developed by the Lifebrain Consortium in Europe. The survey was distributed in both English and Arabic language via social media and the snowball technique. Data analysis included descriptive statistics and results of multivariable binary logistic regression.ResultsA total of 931 responses were recorded and analyzed. Overall, participants demonstrated a moderate understanding of brain health. Key factors that participants believed to influence brain health were physical health, sleep habits, substance use, and social environment. Older participants were more likely to engage in healthy lifestyle choices, while younger participants prioritized different activities. We also observed gender differences, with women less likely to engage in activities such as taking nutritional supplements and practicing relaxation techniques. Higher education and healthcare experience were linked to more informed perceptions of brain health.DiscussionOur findings provide valuable insights into how cultural, social, and demographic factors influence the practices and beliefs toward brain health in the UAE. By adapting the Global Brain Health Survey for a Middle Eastern context, we demonstrate its cross-cultural applicability and contribute to the global discourse on brain health. Our results may inform future public health policies and interventions, highlighting the importance of tailored culturally sensitive strategies to promote brain health across different demographic groups, particularly in multicultural and rapidly aging societies.